Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
The spike in Slovenian inflation in 2007-08 has shown how structural bottlenecks may hamper Slovenian growth in the future. This Selected Issues paper investigates the role of supply factors and demand-side effects in explaining this surge. The paper concludes that the spike in Slovenian inflation in 2007-08 was a consequence of cost-push and demand-pull factors. The supply-side factors, including the spike in commodity prices and demand-pull factors related to the business cycle, explained approximately two-thirds of the surge.